2021
DOI: 10.21203/rs.3.rs-632675/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the Effectiveness of BOPPPS-Based Hybrid Teaching Model in Physiology Education

Abstract: Background: Online teaching has become increasingly common in higher education, of the post-pandemic era. While a traditional face-to-face lecture or offline teaching remains very important and necessary for students to learn the medical knowledge systematically, guided by the BOPPPS teaching model, combination of online and offline learning approaches has become an unavoidable trend for maximizing teaching efficiency. However, in physiological education, the effectiveness of a combined online teaching and off… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…During the internship, they have to manage patients independently and prepare to presentation the case, so they have to fully engaged. In our study, 86.8% of the interns in the experimental group thought the hybrid BOPPPS has helped to stimulate their interest in learning and 88.4% thought it helped to cultivate their ability of self-study, which is identical to the result of the past study [7]. So, the intern-centered teaching model was conducive to the cultivation of interns' active thinking ability.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…During the internship, they have to manage patients independently and prepare to presentation the case, so they have to fully engaged. In our study, 86.8% of the interns in the experimental group thought the hybrid BOPPPS has helped to stimulate their interest in learning and 88.4% thought it helped to cultivate their ability of self-study, which is identical to the result of the past study [7]. So, the intern-centered teaching model was conducive to the cultivation of interns' active thinking ability.…”
Section: Discussionmentioning
confidence: 59%
“…This also impose a signi cant psychological distress for interns, meanwhile they suffer from a lack of clinical opportunity to practice [9]. Hybrid BOPPPS teaching model emphasizes intern-centered and all-round participation, which provide more opportunities for interns to practice [2,7]. Before internship, we uploaded relevant resources on the online teaching platform, including typical representative cases of gynecological common diseases, relevant latest literature, videos and pictures of clinical operations and listed the speci c requirements of the course, which was designed as a selflearning resource for interns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, we found that there was little difference in the number of students between the experimental group and the control group when the score was above 90 and below 70. We observed that when the scores were between 70-79, the number of students in the control group (15) was more than that of the students in the experimental group (9). On the contrary, in the score range of 80-89, the proportion of students in the experimental group (23) was significantly higher than that in the control group (13), indicating that most of the students in the experimental group were in this score range.…”
Section: Discussionmentioning
confidence: 69%
“…BOPPPS model has been used in the practical teaching of many subjects, including dental materials education [13], oral histopathology [14], physiology education [15], healthcare and management education [16]. However, there is no report on the application of BOPPPS model in thoracic surgery education, whether in China or other countries.…”
Section: Introductionmentioning
confidence: 99%